Fruit and vegetable consumption of last grade medical students and related factors - Borlu, Arda; Aykut, Mualla; Çelik, Neslihan; Gün, İskender and Timur, Ahmet and Karaca, Sabri (Progress in Nutrition, 2019)
Objective: This study aimed to determine consumption of fruit and vegetable (F&V) among last grade medical students who will have important roles in community nutrition and health. Material methods: This cross-sectional study was conducted on 246 last grade students of Erciyes University School of Medicine (Kayseri, Central Anatolian, Turkey) at 2014-2015 academic terms in June and July 2015.We examined gender, accommodation, marital status, family type, number of individuals living together, homeland, weight and socioeconomic status, number of meals, having regular snacks, eating away from home, water intake, tobacco and alcohol using, regular physical activity. Weight and height was measured and BMI was calculated. Main outcome measure was the intake of F&V by WHO recommendations. Percentage values were used for qualitative data. Comparisons between eating and health habits and adequacy of F&V intake were analyzed using chi-square test. Results: Only 38.6 % of students consumed adequate F&V. Rate of adequate F&V intake was higher in students who had regular snacks, ate away from home less than once a week, used no tobacco and lived not alone. Conclusions and Implications: The adequate consumption of F&V among last grade medical students’ was low. Knowledge and behaviors of last grade medical students about F&V consumption must be improved.